Feasibility of the quantification of respirable crystalline silica by mass on aerosol sampling filters using Raman microscopy. (20th February 2017) - Stacey, Peter; Mader, Kerstin T.; Sammon, Christopher
Abstract : Airborne respirable crystalline silica (RCS) is a hazard that can affect the health of workers, and more sensitive measurements are needed for the assessment of worker exposure. To assess the use of Raman microscopy for the analysis of RCS particulate collected on filters, aliquots of quartz or cristobalite suspended in isopropanol were pipetted onto silver filters. Samples were measured by arbitrarily selecting positions along the filter and collecting spectra at 50 discrete points. The calculated limits of quantification on test samples were between 0.066–0.161 and 0.106–0.218 μg for quartz and cristobalite, respectively. Three respirable quartz calibration dusts (A9950, NIST 1878 and Quin 1B) with different mass median aerodynamic particle sizes obtained similar Raman response relationships per unit mass. The difference between NIST 1878 and Quin 1B was not significant ( p  = 0.22). The intermediate measurement precision of replicate samples was 10–25% over the measured range for quartz (0.25–10 μg) and could potentially be improved. Results from mixtures of quartz and cristobalite were mostly within 10% of their theoretical values. Results from samples of 6% quartz in calcite were close to the theoretical quartz mass. The upper measurement limit for a mixture of 20% RCS in the light absorbing mineral hematite (Fe2 O3 ) was 5 μg. These data show that Raman spectroscopy is a viable option for the quantification of the mass of respirable crystalline silica on filters with a limit of detection approaching 1/10th of that obtained with other techniques. The improvement in sensitivity may enable the measurement of particulate in samples from low concentration environments (e.g. inside a mask) or from miniature samplers operating at low flow rates. ©2017 Crown copyright. Journal of Raman Spectroscopy published by John Wiley & Sons, Ltd. © 2017 Crown copyright. Journal of Raman Spectroscopy published by John Wiley & Sons, Ltd. Abstract : Airborne respirable crystalline silica is hazardous, and more sensitive measurements are needed for exposure assessment. Limits of detection obtained on silver filters were ten times lower than reported by current Infrared or X‐ray diffraction methods. Differences in median aerodynamic particle size of calibration dusts did not affect the Raman response. Respirable crystalline silica was measured in mixtures of 94% calcite and 80% hematite. Absorption of Raman response by opaque hematite particles occurred above a 'critical' loading.